2017
DOI: 10.2147/eb.s140481
|View full text |Cite
|
Sign up to set email alerts
|

Visual consequences of medications for multiple sclerosis: the good, the bad, the ugly, and the unknown

Abstract: Multiple sclerosis (MS) is associated with vision changes both due to MS effects on visual pathways and due to medication effects on the visual pathways. Distinguishing the causes of vision change are critical to appropriate diagnosis and management. The incidence, presentation, and treatment of fingolimod-associated macular edema, alemtuzumab-associated thyroid orbitopathy, and progressive multifocal leukoencephalopathy in MS patients are reviewed. Evidence for beneficial effects of acute, chronic, and sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…The time course informs monitoring and management. Our six patients fit previous studies which report the onset of Graves' disease ranging from 6 months to 7 years but with a peak at around 18-36 months [15,21] which coincides with when the B-cells are reconstituted and later peak.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The time course informs monitoring and management. Our six patients fit previous studies which report the onset of Graves' disease ranging from 6 months to 7 years but with a peak at around 18-36 months [15,21] which coincides with when the B-cells are reconstituted and later peak.…”
Section: Discussionsupporting
confidence: 90%
“…Development of thyroid eye disease is less common, occurring in less than 2% of alemtuzumab-treated MS patients [21]. Consequently, only a handful of cases have been reported in the literature (see Table 2) [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, based on available data, fingolimod seems to have some short-term benefit in T1D by downregulating the immune response against beta-cell, but long-term responses are missing as it fails to halt disease progression. Furthermore, it must be kept in mind that in diabetic patients the risk for developing macula edema under fingolimod is increased (Moss, 2017). This risk must be weighed against its rather limited benefit as an insulin sensitizer in diabetes.…”
Section: Insulin Resistancementioning
confidence: 99%
“…Those seen more frequently with fingolimod than with placebo included lymphopenia, increased liver transaminases, herpes viral infections, hypertension, and initial bradycardia and first degree AV block both as first-dose effects. Of note, analysis of pooled safety data from various phase 2 and phase 3 studies revealed that the risk for macular edema, which in FREEDOMS II occurred in 1% of the patients in both the fingolimod and the placebo group, was seven times more common in individuals with coexisting diabetes or history of uveitis when treated with 1.25 mg fingolimod (Moss, 2017;Zarbin et al, 2013).…”
Section: Other Potential Indications For Fingolimodmentioning
confidence: 99%
“…In fact, although corticosteroids may reduce inflammation and stimulate acute visual recovery, up to 60% of patients fail to normalize visual function (see [ 7 ]). Additional newer candidates to improve ON function have been recently established, although their benefit and harm remain to be determined (see [ 8 ]).…”
Section: Introductionmentioning
confidence: 99%